Shape Engineering of TiO2 Microrobots for "On‐the‐Fly" Optical Brake. Issue 10 (18th December 2021) - Oral, Cagatay M.; Ussia, Martina; Yavuz, Derya Kapusuz; Pumera, Martin
Abstract: Hybrid microrobots have recently attracted attention due to their ability to combine different energy sources and/or external stimuli for propulsion and performing desired tasks. Despite progresses in the past, on‐demand speed modulation for hybrid microrobots has not been analyzed in detail. Herein, the influence of surface properties and crystallite size on the propulsion mechanism of Pt/TiO2 chemical/light‐driven hybrid microrobots is investigated. The morphology of urchin‐like Pt/TiO2 microrobots leads to "on‐the‐fly" optical brake behavior under UV irradiation. In contrast, smooth Pt/TiO2 microrobots demonstrate accelerated motion in the same conditions. The comparison between two types of microrobots also indicates the significance of a high surface area and a high crystallite size to increase their speed. The results demonstrate the profound impact of surface features for next‐generation smart micro/nanorobots with on‐demand reaction capability in dynamically changing environments. Abstract : On‐demand speed modulation for Pt/TiO2 microrobots is presented via particle engineering. Urchin‐like morphology of the microrobots leads to an "on‐the‐fly" optical brake under UV irradiation. In contrast, smooth microrobots demonstrate accelerated motion in the same conditions. The comparison between the microrobots also highlights the strong influence of surface area and crystallite size on microrobot speed.